Robots, occupations, and worker age: A production-unit analysis of employment - Liuchun Deng; Steffen Müller; Verena Plümpe; Jens Stegmaier (Halle Institute for Economic Research (IWH), 2023)
We analyse the impact of robot adoption on employment composition using novel micro data on robot use in German manufacturing plants linked with social security records and data on job tasks. Our task-based model predicts more favourable employment effects for the least routine-task intensive occupations and for young workers, with the latter being better at adapting to change. An event-study analysis of robot adoption confirms both predictions. We do not find adverse employment effects for any occupational or age group, but churning among low-skilled workers rises sharply. We conclude that the displacement effect of robots is occupation biased but age neutral, whereas the reinstatement effect is age biased and benefits young workers most.
urn:nbn:de:gbv:3:2-937504
Keywords: D22; J23; J24; O33; 330; automation; employment; industrial robots; occupation; worker age; workforce composition